Intra-articular bone marrow mononuclear cell therapy improves lameness from naturally occurring equine osteoarthritis - Everett, J. Blake; Menarim, Bruno C.; Barrett, Sarah H.; Bogers, Sophie H.; Byron, Christopher R.; Pleasant, R. Scott; Werre, Stephen R.; Dahlgren, Linda A. (Frontiers in Veterinary Science, 2023)
Osteoarthritis (OA) can be debilitating and is related to impaired resolution of synovial inflammation. Current treatments offer temporary relief of clinical signs, but have potentially deleterious side effects. Bone marrow mononuclear cells (BMNC) are a rich source of macrophage progenitors that have the ability to reduce OA symptoms in people and inflammation in experimentally-induced synovitis in horses. The objective of this study was to evaluate the ability of intra-articular BMNC therapy to improve clinical signs of naturally occurring equine OA. Horses presenting with clinical and radiographic evidence of moderate OA in a single joint were randomly assigned to 1 of 3 treatment groups: saline (negative control), triamcinolone (positive control), or BMNC (treatment group). Lameness was evaluated subjectively and objectively, joint circumference measured, and synovial fluid collected for cytology and growth factor/cytokine quantification at 0, 7, and 21 days post-injection. Data were analyzed using General Estimating Equations with significance set at P<0.05. There were no adverse effects noted in any treatment group. There was a significant increase in synovial fluid total nucleated cell count in the BMNC-treated group on day 7 (median 440; range 20-1920 cells/uL) compared to day 0. Mononuclear cells were the predominant cell type across treatments at all time points. Joint circumference decreased significantly in the BMNC-treated group from days 7 to 21 and was significantly lower at day 21 in the BMNC-treated group compared to the saline-treated group. Median objective lameness improved significantly in the BMNC group between days 7 and 21. GM-CSF, IL-1ra, IGF-1, and TNF-α were below detectable limits and IL-6, IL-1β, FGF-2 were detectable in a limited number of synovial fluid samples. Inconsistent and limited differences were detected over time and between treatment groups for synovial fluid PGE2, SDF-1, MCP-1 and IL-10. Decreased lameness and joint circumference, coupled with a lack of adverse effects following BMNC treatment, support a larger clinical trial using BMNC therapy to treat OA in horses.